The Tradition of Tulak Breuh as a Fidyah of Prayer in Aceh Besar Society: A Study of Law Theology - Hakim, Lukman; Long, Ahmad Sunawari (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Tulak Breuh is a customary practice related to Islamic law and theology in the social life of the Acehnese people. This article discusses the discourse on fidyah of prayer in fiqh, the practice of the tulak breuh tradition, and the analysis of law theology on the practice of tulak breuh tradition. The methods of study combine library research and field research simultaneously. Data collection techniques were conducted through interviews and literature studies. From the results of research conducted, it is found that there are two opinions of ulema regarding the fidyah of prayer. The first is the Hanafi madhab and some of the Shafi'iyah ulema who allow the practice of fidyah of prayer. The second is Maliki, Hanbali, and Shafi'i madhab (a strong mu'tamad) do not allow the practice of fidyah of prayer. The opinion that allows fidyah of prayer is based on the qiyas of the existence of fidyah for people who leave fasting and the fact that everyone must have left his prayer during his lifetime. Meanwhile, those who claim there is no fidyah for prayer are due to the strict prohibition against leaving prayer and there is unacceptable for a Muslim to leave a prayer. A special team, who is intentionally invited to pay fidyah when someone dies, organizes the implementation of tulak breuh tradition. The implementation of tulak breuh is done by handing over the amount of rice in turn as a substitute for the missed prayers by the deceased. However, theologically, the tulak breuh tradition can have implications for the emergence of a permissive attitude towards prayer as one of the pillars of Islam. Because this tradition provides opportunities and concerns, a lay believer can quickly leave prayer because he is sure that his heirs will redeem his missed prayers with fidyah when he dies.